PARENTING ITU PENTING: PENGABDIAN PADA MASYARALAT DESA. BOJONG, KAB. PANGANDARAN - Hamidah, Nida Hawwa; Rizqi, Anggi Maulana (Perkumpulan Pendidikan Islam Anak Usia Dini Wilayah Sumatera, 2024)
This research aims to help teachers and parents deal with and pay attention to each child's growth and development. The method for implementing community service programs is carried out in several stages, namely: planning stage, implementation stage and evaluation stage. Parenting seminar activities will be held on Thursday, June 6 2024, inviting RA/TK throughout Bojong Village. The implementation of this parenting seminar was of course motivated by the results of observations made by the service team at each PAUD institution, especially in Bojong Village, Panagandaran Regency, with the aim of helping teachers and parents in solving existing problems. This article will review several key aspects of community service activities in the context of parenting, including how to educate children, the importance of collaboration between parents and service providers, and the positive impacts that can be achieved through this joint effort. And through this activity, it is hoped that all parents of students will be able to: increase knowledge and skills, strengthen parent-child relationships, collaborate between parents and teachers.